Evaluasi Economic Value Added (EVA), Financial Value Added (FVA) dan Market Value Added (MVA) dengan Time Series Approach Sebagai Alat Penilaian Kinerja Keuangan. ( Pada PT. Garuda Indonesia Tbk Periode 2015-2019) - Diyanti Rifal Agustin; Ni Nyoman Putu Martini; Tatit Diansari Riskiputri (Jurnal Manajerial, 2021)
Background – Financial performance is a company's work performance that has been achieved in a certain period and can be seen in the financial statements of the company concerned. Financial statement analysis using conventional methods is often used by companies to measure their financial performance, namely financial ratio analysis. PT Garuda Indonesia Tbk, must have the option to create value added or large profits and create or add value to the capital that has been donated to meet the assumptions for financial backers (financial backers or investors). Purpose – Measure financial performance with Economic Value Added (EVA), Financial Value Added (FVA) and Market Value Added (MVA). Design/ Methodology/ Approach – This is a descriptive research with a quantitative approach. Sources of data in this study using external secondary data sources obtained through literature study which is arranged in the form of documents in the form of financial reports. The analysis technique in this study uses Time Series Analysis. Results and Discussion - EVA measurement with a time series approach from 2015-2019 the average EVA is -25,291,800.85, this indicates that the company has not been able to provide added value to shareholders because EVA is negative (EVA<0) so it is said to perform Not Good. Measurement of FVA with a time series approach from 2015-2019 the average FVA is 21,359,193.35, this indicates that the company is able to provide added financial value for companies and investors because the FVA value is Positive (FVA> 0) so it is said to be performing well . MVA measurement with a time series approach from 2015-2019 the average MVA is 9,019.927,024,116, this indicates that the company is able to provide added value because the MVA value is Positive (MVA> 0) so it is said to be performing well. Conclusion – EVA, FVA, and MVA values ​​in 2015 were positive, in 2016 EVA and FVA were negative while MVA was positive, in 2017 EVA was negative while FVA and MVA were positive, in 2018 EVA was negative, FVA and MVA were positive, in 2018 2019 EVA, FVA, and MVA are positive. Research Implications - The research results in this study can be considered by the management of PT Garuda Indonesia in assessing and evaluating the company's financial performance.